Legal Protection for Children Involved in Terrorism Crimes - Chiara, Ni Putu Ayu Mandalay Shasa Alba; Bagiastra, I Nyoman (IJBLE Scientific Publications Community Inc., 2026)
Children are the nation's future generation whose rights are constitutionally guaranteed, yet contemporary crime developments indicate that children are not only victims but also perpetrators of criminal acts, including terrorism, which is classified as an extraordinary crime. The involvement of children in terrorist networks raises serious legal issues concerning criminal responsibility and the protection of children’s rights. This study aims to analyze the legal regulation of children who commit terrorism offenses and the forms of legal protection afforded to them under Indonesian law. This research employs a normative legal method, using statutory and conceptual approaches, to examine Law Number 11 of 2012 on the Juvenile Criminal Justice System, Law Number 35 of 2014 on Child Protection, and Law Number 5 of 2018 on the Eradication of Terrorism Crimes. The findings indicate that the legal framework applies the principle of lex specialis derogat legi generali in handling children involved in terrorism. Children are positioned not merely as offenders but as victims of ideological exploitation within organized networks. Consequently, legal treatment prioritizes rehabilitation, education, social reintegration, and restorative justice rather than retributive punishment. This approach is intended to safeguard the best interests of the child while maintaining the objectives of law enforcement and public security.